INTERACTIVE CORRECTION OF AUTOMATICALLY DESIGNED RATIONAL CUTTING SCHEMES FOR RECTANGULAR MATERIALS ON LEATHER GOODS PARTS - CHUPRYNKA, VIKTOR; NAUMENKO, BOGDAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper considers one of the important tasks of automated design of rational cutting schemes for rectangular materials on leather goods parts, namely the task of interactive correction of automatically designed rational cutting schemes for rectangular materials on leather goods parts. To successfully solve this task, the technological and mathematical formulation of this task is given. In the task of interactive design of cutting schemes for rolled materials for leather goods parts, the following main structural components for the mathematical model were identified and an analytical description of each of these components is presented: analytical representation of the material configuration; analytical representation of information about the external contours of the parts being placed; parameters that determine the location of parts on the plane; analytical description of conditions that prevent the intersection of parts with the edges of the material; the ability to identify each part on the material; ensuring mutual non-intersection of the active part with parts that are already in the cutting scheme; analytical formulation of the objective function. For the description of structural components: - the ability to identify each part on the material; - to ensure mutual non-intersection of the active part with the parts that are already in the cutting scheme, the method of angles was used, which allows to uniquely identify the mutual placement of the point and the polygon (the active point is inside the polygon or outside it). Using the analytical description of the selected structural components, algorithms for implementing this task were proposed in a software product for interactive correction of rational cutting schemes designed in automatic mode for rectangular materials into leather goods parts. The developed software product has a friendly interface and does not require additional knowledge of computer science when working with it. This product can be useful in preparatory and cutting production in light industry.
Keywords: cutting scheme; haberdashery; algorithm; software product; interactive adjustment; corner method; rectangular material